Effects of artocarpus heterophyllus and morus alba extracts on blood glucose, lipid profile and oxidative stress in STZ-Induced diabetic rats - Marwa Ahmed Ali Ali Abdeen; Mohamed T. Abdelraheem; Moustafa M. Said; Samy A. Abdelazim (Cairo : Marwa Ahmed Ali Ali Abdeen, 2016)
In traditional medicine, morus alba (mulberry) and artocarpus heterophyllus (jackfruit) leaves extracts (MLE and JLE) were used for the treatment of diabetes mellitus. Current study was conducted to evaluate the efficacy of MLE and JLE, alone or in combination, compared to gliclazide, on streptozotocin-nicotinamide-induced diabetic rats for weeks. For both extracts, acute oral toxicity studies were carried out; total polyphenols and flavonoids were colourimetrically assayed; and different phenolic compounds and flavonoids were HPLC-assayed. Diabetes was induced in rats by a single intraperitoneal injection of streptozotocin (65 mg/kg b.w.), 15 min after the intraperitoneal injection of nicotinamide (110 mg/kg b.w.). Our observations demonstrated no signs of acute oral toxicity both extracts up to 5 g/kg b.w, beside the presence of many flavonoids and polyphenols, including hisperedin, rutin, vitexin, hisperetin, OH-Tyrosol, benzoic, chicoric and e-vanillic acids. Results also showed that diabetic rats had significant increase in fasting plasma glucose, glycated haemoglobin, all lipid profile parameters except HDL, malondialdehyde, oxide and liver tissues DNA damage levels compared to normal controls, whereas, liver glycogen, erythrocytes glutathione levels, superoxide dismutase and catalase activities were significantly decreased. Fasting plasma glucose levels and glycated haemoglobin were significantly decreased by treatment with MLE or JLE, and normalized by gliclazide. Treatment of diabetic rats with either MLE, JLE or in combination caused significant decrease of the elevated lipid profile parameters. Alterations in plasma malondialdehyde, glutathione and nitric oxide levels were reverted to near normal with MLE and combination, respectively
Thesis (M.Sc.) - Cairo University - Faculty of Pharmacy - Department of Biochemistry
Issued also as CD
Keywords: Artocarpus; Gliclazide; Morus